PERANCANGAN BRAND IDENTITY XINXIN HOME INDUSTRY BERBASIS NATURE SEBAGAI UPAYA PENINGKATAN BRAND AWARENESS - Hidayat, Galih Rendy; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of designing brand identity Xinxin is to increase efforts to promote the new company and brand awareness to the general public. The research was conducted using qualitative research method is to conduct interviews, observation, documentation, and literature to get the data used to support the drafting of designing brand identity. Data were analyzed using multiple stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to branding communications strategy that will be used to reach the intended target audience. After analyzing the data, found a concept or keyword designing brand identity that is "Excellent". Description of the concept of "Excellent" is an advantage or a quality possessed by the products offered on Xinxin Home Industry. In this case the "Excellent" or superiority is evidence of such beverage products Xinxin naturally uses the basic elements of nature on the quality and packed with emphasis on health and classy impression on any product offered. Results from the design brand identity is an effort to help increase brand awareness and promotion of a new company in particular is Xinxin Home Industry in the minds of your target market or society at large. Keywords: Brand Identity, Xinxin, Black Cincau Beverages, Processed Leaf Cincau